The impact of the COVID‐19 pandemic on African American cancer survivors. Issue 4 (27th October 2021) - Beebe‐Dimmer, Jennifer L.; Lusk, Christine M.; Ruterbusch, Julie J.; Baird, Tara E.; Pandolfi, Stephanie S.; Wenzlaff, Angela S.; Hastert, Theresa A.; Harper, Felicity W. K.; Thompson, Hayley S.; Schwartz, Ann G.
Abstract : Background: Coronavirus disease 2019 (COVID‐19) has had profound effects on population health to date. African American cancer survivors are particularly vulnerable to developing severe consequences; therefore, understanding the impact of the virus on this patient population is critical. Methods: The Detroit Research on Cancer Survivors cohort is a unique effort to understand the determinants of poor outcomes in African American cancer survivors. To date, more than 4500 cancer survivors and nearly 950 primary caregivers have been enrolled; participation includes a survey and the collection of biospecimens, medical records, and tumor tissue. Beginning in the spring of 2020, a supplemental survey focusing on the impact of COVID‐19 was offered to enrolled participants. The analysis included 890 survivors. Results: Nearly all survivors (>99%) reported changes in their daily activities in an effort to reduce the risk of infection. More than 40% of the survivors reported some disruption in their access to medical care. A substantial proportion of the survivors (>40%) reported feeling anxious, depressed, and/or isolated during the COVID‐19 pandemic. Approximately 40% of the patients reported changes in health behaviors shown to negatively affect survivorship outcomes (physical inactivity, smoking, and alcohol use) as a result of the pandemic. Conclusions: The influence of the COVID‐19 pandemic on African American cancer survivors is substantial: it has affected both their physical and mental health. Coupled with changes in health behaviors, these factors will likely affect outcomes in this high‐risk patient population, and this makes further study and interventions necessary to mitigate the long‐term impact of the pandemic on cancer outcomes. Abstract : The COVID‐19 pandemic has had a profound impact on the physical and mental health of African American cancer survivors living in Detroit, Michigan. Strategies focusing on health behaviors such as physical activity would improve patient health and quality of life.